Graphene oxide/MIL 101(Cr) (GO/MOF) nano-composite for adsorptive removal of 2, 4-dichlorophenoxyacetic acid (2, 4 D) from aqueous media: synthesis, characterization, kinetic and isotherm studies. (3rd September 2022) - Khaloo, Shokooh Sadat; Bagheri, Amin; Gholamnia, Reza; Saeedi, Reza
Abstract: Contamination of water resources with various pollutants and therefore lack of clean water resources are major problems that threaten many human societies. The need to develop efficient methods and materials to decontaminate water resource is an undeniable fact. Metal-organic frameworks (MOFs), as new class of highly crystalline porous solids, have attracted a great deal of attention in different research fields, especially in adsorptive removal and purification. In this study, MIL 101(Cr) MOF decorated with graphene oxide nano-layers (GO/MOF) was synthesized by a simple one-pot hydrothermal method. Scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and electron dispersion energy (EDS) were utilized to approve the growing of Cr-MOF on graphene oxide nano-layer. The synthesized nano-composite was used as a potential adsorbent for the removal of a pesticide, 2, 4-dichlorophenoxyacetic acid (2, 4 D). The adsorption performance, kinetic and mechanism of 2, 4 D adsorption onto GO/MOF were studied. The highest adsorption capacities of 476.9 mg g −1 was obtained at room temperature, pH 6.0 using 0.6 gL −1 of GO/MOF which was 34% higher than that of pristine Cr-MOF. The kinetics and isotherm data fitted well with pseudo-second kinetic and Langmuir isotherm model, respectively. The reusability and stability analyses showed that the synthesized GO/MOF nanocomposite kept 89% of sorption capacities for 2, 4 D after four adsorption–desorption cycles. GO/MOF nano-composite was successfully applied to remove 2, 4 D from agricultural waste. The results approved that the synthesized nano-composite could introduce as a stable and high performance adsorbent for adsorptive removal of selected pesticide. HIGHLIGHTS: Graphene oxide nano-sheet decorated by MIL 101(Cr) has been synthesized by the hydrothermal method and characterized by SEM, EDS, XRD and FT-IR technology. Adsorption kinetic, isotherm, reusability and stability of the nano-composite GO/MOF (Cr) in removal of 2, 4 D pesticide were studied. Applicability of the nano-composite GO/MOF (Cr) in removal of 2, 4 D pesticide in agricultural wastewater was approved.